A Program of Exercise Throughout Pregnancy. Is it Safe to Mother and Newborn?. Issue 1 (September 2014) - Barakat, Ruben; Perales, Maria; Bacchi, Mariano; Coteron, Javier; Refoyo, Ignacio
Purpose: The aim of the present study was to examine the influence of a program of moderate physical exercise throughout pregnancy on maternal and fetal parameters. Design: The study design was a randomized controlled trial. Setting: The study took place at the Hospital of Fuenlabrada in Madrid, Spain. Sample: Analyzed were 200 pregnant women (31.54 ± 3.86 years), all of whom had uncomplicated and singleton gestation. Of these subjects, 107 were allocated to the exercise group (EG) and 93 to the control group (CG). Intervention: Women from EG participated in a physical conditioning program throughout pregnancy, which included a total of 55- to 60-minute weekly sessions, 3 days per week. Measures: Pregnancy outcomes. Maternal: gestational age, weight gain, type of delivery, blood pressure during pregnancy, gestational diabetes (n/%). Fetal: birth weight, birth size, head circumference, Apgar score, pH of umbilical cord. Analysis: Student's unpaired t-test and χ 2 test were used; p values of ≤ .05 indicated statistical significance. Cohen's d was used to determine the effect size. Results: There were significantly more pregnant women in the CG who gained excessive weight during their pregnancies than in the EG group (CG: N = 31, 35.6% versus N = 22, 21.2%; χ 2 = 4.95; p =.02). The effect size was small (Phi value =.16). Other pregnancy outcome showed no differences between groups. Conclusion: A regular and moderate physical exercise program throughout pregnancy is not a risk to maternal and fetal well-being, and it helps to control excessive weight gain.